Abdominoplasty Skin-Based Dressing for Deep Wound Treatment-Evaluation of Different Methods of Preparation on Therapeutic Potential - Dawid Groth; Izabela Poplawska; Marlena Tynecka; Kamil Grubczak; Jordan Holl; Aleksandra Starosz; Adrian Janucik; Klaudia Borkowska; Dorota Juchniewicz; Hady Razak Hady; Slawomir Czaban; Joanna Reszec; et al. (MDPI AG, 2021)
The management of hard-to-heal wounds is a significant clinical challenge. Acellular dermal matrices (ADMs) have been successfully introduced to enhance the healing process. Here, we aimed to develop protocol for the preparation of novel ADMs from abdominoplasty skin. We used three different decellularization protocols for skin processing, namely, 1M NaCl and sodium dodecyl sulfate (SDS, in ADM1); 2M NaCl and sodium dodecyl sulfate (SDS, in ADM1); and a combination of recombinant trypsin and Triton X-100 (in hADM 3). We assessed the effectiveness of decellularization and ADM's structure by using histochemical and immunochemical staining. In addition, we evaluated the therapeutic potential of novel ADMs in a murine model of wound healing. Furthermore, targeted transcriptomic profiling of genes associated with wound healing was performed. First, we found that all three proposed methods of decellularization effectively removed cellular components from abdominoplasty skin. We showed, however, significant differences in the presence of class I human leukocyte antigen (HLA class I ABC), Talin 1/2, and chondroitin sulfate proteoglycan (NG2). In addition, we found that protocols, when utilized differentially, influenced the preservation of types I, III, IV, and VII collagens. Finally, we showed that abdominoplasty skin-derived ADMs might serve as an effective and safe option for deep wound treatment. More importantly, our novel dressing (ADM1) improves the kinetics of wound closure and scar maturation in the proliferative and remodeling phases of wound healing. In conclusion, we developed a protocol for abdominoplasty skin decellularization suitable for the preparation of biological dressings. We showed that different decellularization methods affect the purity, structure, and therapeutic properties of ADMs.